Lionboy : the first book in a trilogy - Corder, Zizou (New York : Puffin Books, 2004)
In the near future, a boy with the ability to speak the language of cats sets out from London to seek his kidnapped parents and finds himself on a Paris-bound circus ship learning to train lions.
6.3
5-8
5-8
Wilson's Junior High School
School Library Journal
Pub Weekly
Keywords: Human-animal communication -- Fiction; Kidnapping -- Fiction; Cats -- Fiction; Lions -- Fiction; Circus -- Fiction; Voyages and travels -- Fiction; Human-animal communication -- Fiction; Kidnapping -- Fiction; Cats -- Fiction; Lions -- Fiction; Circus -- Fiction; Voyages and travels -- Fiction